Tualang Honey Protects against BPA-Induced Morphological Abnormalities and Disruption of ERα, ERβ, and C3 mRNA and Protein Expressions in the Uterus of Rats. (14th December 2015) - Mohamad Zaid, Siti Sarah; Kassim, Normadiah M.; Othman, Shatrah
Abstract : Bisphenol A (BPA) is an endocrine disrupting chemical (EDC) that can disrupt the normal functions of the reproductive system. The objective of the study is to investigate the potential protective effects of Tualang honey against BPA-induced uterine toxicity in pubertal rats. The rats were administered with BPA by oral gavage over a period of six weeks. Uterine toxicity in BPA-exposed rats was determined by the degree of the morphological abnormalities, increased lipid peroxidation, and dysregulated expression and distribution of ER α, ER β, and C3 as compared to the control rats. Concurrent treatment of rats with BPA and Tualang honey significantly improved the uterine morphological abnormalities, reduced lipid peroxidation, and normalized ER α, ER β, and C3 expressions and distribution. There were no abnormal changes observed in rats treated with Tualang honey alone, comparable with the control rats. In conclusion, Tualang honey has potential roles in protecting the uterus from BPA-induced toxicity, possibly accounted for by its phytochemical properties.